2011
DOI: 10.4061/2011/489342
|View full text |Cite
|
Sign up to set email alerts
|

Gadoxetate Acid-Enhanced MR Imaging for HCC: A Review for Clinicians

Abstract: Hepatocellular carcinoma (HCC) is increasingly being detected at an earlier stage, owing to the screening programs and regular imaging follow-up in high-risk populations. Small HCCs still pose diagnostic challenges on imaging due to decreased sensitivity and increased frequency of atypical features. Differentiating early HCC from premalignant or benign nodules is important as management differs and has implications on both the quality of life and the overall survival for the patients. Gadoxetate acid (Gd-EOB-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 95 publications
(104 reference statements)
2
21
0
3
Order By: Relevance
“…Recent advances in imaging techniques may enable earlier and more accurate diagnosis of HCC . Gadoxetic acid, a liver‐specific contrast agent that is retained by hepatocytes and excreted into the bile ducts , allows monitoring of small lesions over a long period.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in imaging techniques may enable earlier and more accurate diagnosis of HCC . Gadoxetic acid, a liver‐specific contrast agent that is retained by hepatocytes and excreted into the bile ducts , allows monitoring of small lesions over a long period.…”
Section: Discussionmentioning
confidence: 99%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…(b2) 20 min after administration of Gd-eOB-dTpA, the high contrast allows a better diagnosis of the tumor (Reprinted with permission from Ref. [37]. © Hindawi publishing Corporation).…”
Section: Approved Gadolinium-based Contrast Agents: Clinical Applicatmentioning
confidence: 99%